Development of Offloading Oil Products Simulations for Petrol Pump Employees Using Virtual Reality : Offload VR - Nasaruddin, Irfan Azan Nasr; Che Dalim, Che Samihah (Applied Information Technology And Computer Science, 2026)
The "Offloading Oil Products Simulations" project uses VR technology to tackle critical training challenges in the oil and gas industry, a key pillar of global economic stability. Traditional training for high-risk tasks, such as offloading oil from tanker trucks, poses hazards like chemical exposure, physical injuries, and inefficiencies. Developed for the Oculus Quest 3, this innovative application provides a fully immersive, interactive environment where users can safely practice complex procedures. Tailored for petrol pump employees at Ujong Pasir, Melaka, the simulator includes four detailed modules—Dipping, Documentation, HSE Preparation, and Quality Check. By employing TRES-D methodology, the project ensures iterative enhancements, seamless functionality, and user-friendly design, significantly reducing costs and safety risks while improving training outcomes. Usability test conducted on 20 petrol pump employees yielded 69.13 score, indicating that the system is acceptable. This initiative sets new standards for productivity, creativity, and workforce readiness in high-risk industries.